2017
DOI: 10.1016/j.jval.2017.08.477
|View full text |Cite
|
Sign up to set email alerts
|

Does the Distance to the Nearest Pharmacy Affect Medication Adherence Rates Among Elderly Patients with Diabetes?

Abstract: A483(75 patients each). The 75 patients on our intervention group were educated by the Pharmacist on diabetes and hypertension, their complications, risks, preventive measures and management. This was done at least six times during the study period unlike the control group who received no such education. In particular, they were counseled on the need for medication and treatment adherence such as clinic visits, and life style modifications including diet and exercise. Outcome measure included changes in fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
1
1
1
Order By: Relevance
“…The finding that geographic distance to pharmacy was not a significant predictor has been demonstrated in previous studies. 4,5 Conversely, the present study found that RI, a measure of 1 dimension of RRS, was significantly associated with adherence, where residence in more isolated areas was associated with lower adherence. Likewise, the SES measure used in the present study found that areas of lower SES had lower levels of adherence to statin drug therapy.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The finding that geographic distance to pharmacy was not a significant predictor has been demonstrated in previous studies. 4,5 Conversely, the present study found that RI, a measure of 1 dimension of RRS, was significantly associated with adherence, where residence in more isolated areas was associated with lower adherence. Likewise, the SES measure used in the present study found that areas of lower SES had lower levels of adherence to statin drug therapy.…”
Section: Discussioncontrasting
confidence: 69%
“…3 Patients may need to travel farther when there is limited access to pharmacies close to home. Generally, studies have found that the distance between home and the pharmacy is not significantly associated with medication adherence 4,5 and that patients may travel beyond their most closely located pharmacy to one they are more satisfied with. 6 A previous study by the investigators found that statin adherence varies significantly across the State of Michigan for an insured sample of patients taking statin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with studies conducted on other chronic diseases (36,37). However, a study in Pennsylvania contrasts this finding (38).This might be due to the socioeconomic differences of study participants.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with studies conducted on other chronic diseases [35,36]. However, a study in Pennsylvania contrast to this finding [37]. This might be due to socio-economic difference of study participants.…”
Section: Socio-demographic Characteristicssupporting
confidence: 90%